EXPLORE THE ROLE OF TECHNOLOGY IN FACILITATING COMMUNICATION AND TRANSNATIONAL CONNECTION (International Journal of Food and Nutritional Sciences, 2022)
The way people communicate has been profoundly affected by recent technology developments. The amount and quality of in-person interactions seem to be declining due to technological advancements, according to several studies. Even though people are aware that technology is reducing face-to-face connection, over 62% of those surveyed on college campuses said they still use their phones when everyone else is around. A number of households have chosen to prohibit electronic devices, including as video games, laptops, and smartphones, in reaction to the excessive amount of time spent in front of the TV. Many are concerned that, with the fast development of technology, people would get too engrossed in their phones and computers to pay attention in the physical world. People are increasingly avoiding face-to-face interactions in favor of conversing via cell phones. Most people think that having a discussion while using a gadget lowers the quality of that conversation, and many people find it annoying when their friends or relatives utilize technological devices while they're around. One of the most important aspects of digital transformation is communication and cooperation